2000
DOI: 10.1108/09566160010321569
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater chemistry as influenced by atmospheric deposition of pollutants in Southern Nigeria

Abstract: Examines rainwater chemistry as it relates to atmospheric pollution in Southern Nigeria. Rainwater samples were collected and analysed for major cations and anions in Lagos, Ibadan and Port Harcourt, these sites reflecting industrial, residential and oil flaring regions respectively. In general, water samples from Ibadan were about neutral. Correlation studies revealed that HCl and H 2 SO 4 dominated the slightly acidic rainwater in the Lagos and Port Harcourt areas respectively. The effect of marine spray fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…(from SO 2 emissions) contribute significantly to acid rain. There is widespread acid rain in the Niger Delta region [31,32,33,43,44], however, there is no information on the relative ratio of SO 4 2− /NO 3 − in precipitation in the region. Acid rain from increased SO 4 2− and NO 3 concentrations is evident in the pH values that range from 4.98 -5.15 and mean value of 5.06 [33].…”
Section: Chemical Biological and Physical Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…(from SO 2 emissions) contribute significantly to acid rain. There is widespread acid rain in the Niger Delta region [31,32,33,43,44], however, there is no information on the relative ratio of SO 4 2− /NO 3 − in precipitation in the region. Acid rain from increased SO 4 2− and NO 3 concentrations is evident in the pH values that range from 4.98 -5.15 and mean value of 5.06 [33].…”
Section: Chemical Biological and Physical Effectmentioning
confidence: 99%
“…Flue gas dispersion, emissions from the flare systems and atmospheric deposition of pollutants have influenced rainwater chemistry in the Nigeria's Niger Delta [31,32,43,44]. The findings from some studies suggest that rainwater from most industrial cities of Nigeria are tending towards acidity and if gas flaring and venting activities are not checked, there is a tendency of increasing acidic rainwater in the Delta regions [32,43]. It is a common practice by many residents in the rural communities to harvest rainwater by capturing runoffs from rooftops for drinking, cooking, laundry and other domestic purposes.…”
Section: Human Health Risksmentioning
confidence: 99%
“…Based on the hot spot characterisation, gas flares can be identified and flared gas volumes and pollutant emissions can be calculated with previously published methods.2 of 28 and global concern. GF impacts the local environment [1] through: noise [2,3], visual pollution [4,5], heat stress [4,6] and the emission of air pollutants like black carbon, polycyclic aromatic hydrocarbons, volatile organic compounds and acid rain precursors [7][8][9][10]. Flaring produces greenhouse gases (GHG) and black carbon as the main by-products of the combustion.…”
mentioning
confidence: 99%
“…It is commonly accepted that rainwater is slightly acidic due to the natural formation of carbonic acids within atmospheric precipitation. Industrial pollution has also been shown to promote acid rain (Uzomah & Sangodoyin 2000), and together with vehicle emissions could explain the more acidic levels observed at the sites.…”
Section: Discussionmentioning
confidence: 98%